Microplastics and human health: unveiling the gut microbiome disruption and chronic disease risks - Bora, Sudipta Sankar; Gogoi, Rahul; Sharma, Madhurjya Ranjan; Anshu,; Borah, Madhurjya Protim; Deka, Priyadarshini; Bora, Jitul; Naorem, Romen Singh; Das, Jugabrata; Teli, Anju Barhai (Frontiers in Cellular and Infection Microbiology, 2024)
Microplastics (MPs), defined as plastic particles smaller than 5 mm, are increasingly recognized as environmental contaminants with potential health risks. These emerge as breakdown products of larger plastics and are omnipresent in marine, freshwater, and terrestrial ecosystems. They are primarily composed of polymers such as polyethylene, polypropylene, polystyrene, and additives that enhance their performance. MPs also adsorb harmful environmental chemicals like persistent organic pollutants and heavy metals, posing risks to human and environmental health. Human exposure to MPs occurs mainly through ingestion and inhalation, with MPs detected in food products, water, and even the air. MPs have been shown to accumulate in the gastrointestinal tract, disrupting the gut microbiome, and causing dysbiosis-a harmful imbalance between beneficial and harmful bacteria. This disruption has been linked to various health issues, including gastrointestinal disorders, systemic inflammation, and chronic diseases. Furthermore, the gut-brain axis may be affected, with potential neuroinflammatory consequences. As research continues to unravel the health impacts of MP exposure, understanding the mechanisms of accumulation and the broader implications on human health is crucial. This review highlights the effects of MPs on human health, emphasizing their impact on the gut microbiome. We discuss the potential connections between MP exposure and cardiometabolic and inflammatory diseases, and disorders related to the Gut-Brain Axis. By synthesizing the latest research, this work sheds light on the silent yet pervasive threat posed by MPs and underscores the importance of further studies to understand their health impacts fully.